Comparative evaluation of liquid-liquid extraction and nanosorbent extraction for HPLC-PDA analysis of cabazitaxel from rat plasma - Suseela M.N.L.; Mehata A.K.; Vallamkonda B.; Gokul P.; Pradhan A.; Pandey J.; Selvin J.; Sterlin Leo Hudson M.; Muthu M.S. (My University, 2025)
A precise, sensitive, accurate, and validated reverse-phase high-performance liquid chromatography (RP-HPLC) method with a bioanalytical approach was utilized to analyze Cabazitaxel (CBZ) in rat plasma. Comparative research on extraction recoveries was performed between traditional liquid-liquid extraction (LLE) and synthesized graphene oxide (GO) based magnetic solid phase extraction (GO@MSPE). The superparamagnetic hybrid nanosorbent was synthesized using the combination of iron oxide and GO and subsequently applied for extraction and bioanalytical quantification of CBZ from plasma by (HPLC-PDA) analysis. Fourier- transform infrared spectroscopy (FT-IR), particle size, scanning electron microscopy (SEM), and x-ray diffraction (XRD) analysis were employed in the characterization of synthesized GO@MSPE nanosorbent. The investigation was accomplished using a shim pack C18 column (150 mm×4.6 mm, 5 µm) with a binary gradient mobile phase consisting of formic acid: acetonitrile: water (0.1:75:25, v/v/v) at a 0.8 mL/min flow rate, and a λmax of 229 nm. The limits of detection (LOD) and quantitation (LOQ) have been determined to be 50 and 100 ng/mL for both LLE and SPE techniques. The linearity range of the approach encompassed from 100 to 5000 ng/mL and was found to be linear (coefficient of determination > 0.99) for CBZ. The proposed method showed extraction recovery of 76.8–88.4% for the synthesized GO@MSPE and 69.3–77.4% for LLE, suggesting that the proposed bioanalytical approach was robust and qualified for all validation parameters within the acceptable criteria. Furthermore, the developed hybrid GO@MSPE nanosorbent with the help of the proposed RP-HPLC method, showed a significant potential for the extraction of CBZ in bioanalysis. © 2024 Elsevier B.V.